Dom versus ściana. Gesty uobecnienia Stanisława Barańczaka w przestrzeni Poznania - Jarmuszkiewicz, Anna (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The article discusses the presentations of Stanisław Barańczak and his poetry in Poznań’s urban space. The poet’s presentification is exemplified by the murals that have been created on the walls of buildings in Poznań after the writer’s death.